2003
DOI: 10.1002/jcc.10228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of quasi‐relativistic density functional methods for the description of lanthanide and actinide complexes

Abstract: We present a comparative Density Functional Theory (DFT) study based on two different implementations of relativistic effects within the Kohn-Sham (KS) approach, to describe the metal-ligand interaction in I(3)M-L complexes (L = NH(3), NCCH(3), CO and M = La, Nd, U). In the first model, the scalar corrections were included by a quasi-relativistic approach (QR) via the so-called ZORA or Pauli Hamiltonians, while in the second, these effects are taken into account in a quasi-Relativistic Effective Core Potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 64 publications
5
84
0
Order By: Relevance
“…It is important to note that the energetic stabilization gained due to 4f covalency is proportional to the overlap between 4f and ligand-based orbitals. 173,175 Hence, because the radial extension of the 4f orbitals is very small, [176][177][178][179] increasing 4f covalency by decreasing the energy separation of the metal and ligand orbitals may act to weaken the bond overall by decreasing the amount of ionic character in the ground state. This work also illustrates that thermodynamic, spectroscopic, and theoretical studies of tetravalent cerium molecules is a fruitful area for research.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the energetic stabilization gained due to 4f covalency is proportional to the overlap between 4f and ligand-based orbitals. 173,175 Hence, because the radial extension of the 4f orbitals is very small, [176][177][178][179] increasing 4f covalency by decreasing the energy separation of the metal and ligand orbitals may act to weaken the bond overall by decreasing the amount of ionic character in the ground state. This work also illustrates that thermodynamic, spectroscopic, and theoretical studies of tetravalent cerium molecules is a fruitful area for research.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] The theoretical treatment of trivalent f elements complexes with ADF has been several times investigated. 29,33,46,47 Density Functional Theory was found to be an effective tool for the description of ground states of the f-elements when applied with the scalar relativistic ZORA approach and the Becke-Perdew GGA functional. 48 In recent papers, the DFT approach was also found to properly reproduce experimental thermodynamic trends, whereas post Hartree-Fock methods (CASPT2, MP2) were required to reach a better quantitative agreement.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As these methods are often used in actinide research, [7,10,[33][34][35] we found it important to devote a discussion to the results. 1 The performance of the three theoretical levels will be compared jointly with the discussion of the characteristic structures in Section 2.1.…”
Section: Introductionmentioning
confidence: 99%